Ministries of Buganda Government, 1894-1967
This includes records on ministries created by Buganda Government a s well as the different departments under certain ministries for exampl e department of Natural resources ( which later became a ministry), dep arment of establishments and department of works which operated under t he Ministry of Economic Planning and Development.
AR/BUG
Luganda and English
Shelf no. 1
Keywords: Executive departments